Translational control of UIS4 protein of the host-parasite interface is mediated by the RNA binding protein Puf2 in plasmodium berghei sporozoites - Silva, Patrícia A. G. C.; Mair, Gunnar R. (PLOS ONE, 2016)
UIS4 is a key protein component of the host-parasite interface in the liver stage of the rodent malaria parasite Plasmodium berghei and required for parasite survival after invasion. In the infectious sporozoite, UIS4 protein has variably been shown to be translated but also been reported to be translationally repressed. Here we show that uis4 mRNA translation is regulated by the P. berghei RNA binding protein Pumilio-2 (PbPuf2 or Puf2 from here on forward) in infectious salivary gland sporozoites in the mosquito vector. Using RNA immunoprecipitation we show that uis4 mRNA is bound by Puf2 in salivary gland sporozoites. In the absence of Puf2, uis4 mRNA translation is de-regulated and UIS4 protein expression upregulated in salivary gland sporozoites. Here, using RNA immunoprecipitation, we reveal the first Puf2-regulated mRNA in this parasite.
Gesehen am 07.05.2020